Far From Home: Adjustment and Social Support Related to Homesickness among Islamic Boarding School Students - Endi Endi; Fadilah Sukma Utami; Faiz Fatihul 'Alwan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Differences in culture and educational systems between public schools and Islamic boarding schools (pesantren) present unique adaptation challenges for students, particularly newcomers. Strict regulations, such as limited opportunities to return home and restricted communication with family, often intensify psychological challenges, including homesickness. If left unaddressed, homesickness may negatively affect students’ psychological well-being and hinder their adjustment process. This study examines the influence of self-adjustment and social support on homesickness among new students at Nurul Iman Islamic Boarding School in Bandung. Using a quantitative causal design, the study involved 81 new students selected through saturated sampling. Data were collected using Likert-scale questionnaires, including the Student Adaptation to College Questionnaire (SACQ), Multidimensional Perceived Social Support Scale (MPSS), and Utrecht Homesickness Scale (UHS), and analyzed using multiple linear regression. The results indicate that self-adjustment and social support together explain a meaningful proportion of variance in homesickness and show a statistically significant negative association, indicating that higher levels of adjustment and perceived social support are associated with lower homesickness. These findings highlight the importance of strengthening students’ adaptive capacities and social support systems and provide practical implications for pesantren administrators in designing programs that facilitate smoother adjustment among new students.